1976
DOI: 10.1085/jgp.68.4.465
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of gamma-aminobutyric acid in the organization of cat retinal ganglion cell receptive fields. A study with picrotoxin and bicuculline.

Abstract: A B S T R A C T The effects of picrotoxin and bicuculline upon the discharge pattern of center-surround organized cat retinal ganglion cells of X and Y type were studied. All experiments were carried out under scotopic or possibly low mesopic conditions; mostly but not exclusively on-center cells were studied. Stimuli were chosen so that responses were either: (a) "purely" central; (b) surround dominated; or (c) clearly mixed but center dominated. In each case a pre-drug control response was established, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

1981
1981
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 33 publications
4
35
1
Order By: Relevance
“…Kirby & Schweitzer-Tong (1981) reported that intravenous injection of GABA antagonists changes the receptive field centre size in Y cells; in an earlier study, it was also reported that X-cell responses remain virtually unaffected by GABA antagonists (Kirby & Enroth-Cugell, 1976). In the present study, we measured area-response curves of the receptive field centre mechanism for two brisksustained(X) cells.…”
Section: Centre Responsementioning
confidence: 95%
See 2 more Smart Citations
“…Kirby & Schweitzer-Tong (1981) reported that intravenous injection of GABA antagonists changes the receptive field centre size in Y cells; in an earlier study, it was also reported that X-cell responses remain virtually unaffected by GABA antagonists (Kirby & Enroth-Cugell, 1976). In the present study, we measured area-response curves of the receptive field centre mechanism for two brisksustained(X) cells.…”
Section: Centre Responsementioning
confidence: 95%
“…During bicuculline this maintained firing level was reduced. Centre and surround stimulation Kirby & Enroth-Cugell (1976) reported that GABA antagonists change the balance of Y-cell receptive fields causing the centre response to become more dominant. In the course of the present study, we occasionally found data which apparently supported this claim, as exemplified by the off-centre brisk-transient(Y) cell shown in Fig.…”
Section: Centre Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Similar effects of strychnine were reported for a variety of species that include an overall increase in the spontaneous and evoked activity ofRGCs when glycinergic transmission is blocked (Burkhardt, 1972, Kirby and Enroth-Cugell, 1976, Miller and Dacheux, 1977. Caldwell et al (1978) .…”
Section: Localization O/glycine Receptors and Retinal Ganglion Cellssupporting
confidence: 73%
“…Thus, it is no surprise that the literature is filled with diverse effects of strychnine in the vertebrate retina and some are conflicting. First, strychnine has been reported to increase ON-and OFF-center RGC's spontaneous and evoked activity at LA levels (Kirby andEnroth-Cugell, 1976, Miller et aI, 1977;Muller et aI, 1988) and block light responses of OFF-but not ON-center RGCs at DA levels (MUller et aI, 1988 (Kirby, 1977;Saito, 1981). Third, strychnine abolishes the transient (Caldwell and Daw, 1978;Belgum et aI, 1983Belgum et aI, , 1984O'Brien et al, 2003) and sustained (Stone and Pinto, 1992) components ofRGC responses.…”
Section: Glycine and The Rf Surroundmentioning
confidence: 99%